Genomic study of Salmonella ser. Enteritidis from poultry farms in Argentina: Epidemiology and antimicrobial resistance in twenty strains - Hoffmann, Teresa Magali; Soria, Mario; Bueno, Dante Javier; Huberman, Yosef Daniel; Ishida, María; Sauders, Brian; Deiulio, Gregory; Dickey, Alyssa Wiedenmayer; Medina-Santana, José Luis; Vinueza-Burgos, Christian (Elsevier, 2025)
The escalating issue of antimicrobial resistance in pathogens transmitted through the food chain poses a significant threat to public health worldwide. Salmonella ser. Enteritidis (SE) remains a predominant cause of foodborne illness. This research aims to elucidate the genetic and antimicrobial resistance profiles of SE strains isolated from Argentine poultry farms. This study used whole genome sequencing to assess the genetic diversity and resistance patterns of 20 SE strains collected from poultry farms in Entre Ríos, Argentina, between January 2020 and February 2021. Phenotypic assays were used to detect resistance to 50 antibiotics across 14 antimicrobial classes. Genes and mutations linked to antimicrobial resistance were pinpointed on both plasmids and chromosomes of the strains. All investigated strains exhibited resistance to nitrofurantoin, and a high percentage showed resistance or intermediate sensitivity to fluoroquinolones. Genomic analysis showed the presence of resistance genes associated with aminoglycosides, β-lactams, and quinolones. The study distinctly categorized the strains into those isolated from broilers and laying hens, highlighting a complex interplay of resistance and diversity within the poultry industry. This shows antimicrobial resistance within foodborne pathogens like SE and the importance of continuous surveillance systems to track the evolution and spread of resistance. The genomic insights from this study not only enhance understanding of the resistance mechanisms but also facilitate tracking the transmission dynamics of SE, which is crucial for developing targeted interventions.